1996
DOI: 10.1016/s1071-3581(96)90020-3
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo investigation of artifacts caused by liver uptake in single-photon emission computed tomography perfusion imaging with technetium 99m-labeled agents

Abstract: The apparent alterations in cardiac counts when significant hepatic localization is present is due to the inconsistency of the projections inherent in imaging. Prior correction of these, or accounting for them in the reconstruction algorithm, will virtually eliminate them as causes of artifactual changes in localization. Attenuation correction and scatter correction are both required to overcome the major sources of apparent count changes in the heart associated with hepatic uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 12 publications
1
26
0
Order By: Relevance
“…In fact, attenuation correction without scatter correction may even promote artifact production. 5,33 …”
Section: Current Trialmentioning
confidence: 99%
“…In fact, attenuation correction without scatter correction may even promote artifact production. 5,33 …”
Section: Current Trialmentioning
confidence: 99%
“…Several experiments have shown that all these degradations have to be corrected for to optimize clinical SPECT images (4)(5)(6)(7)(8)(9). The correction of attenuation and camera blurring is a relatively straightforward and well-established process.…”
mentioning
confidence: 99%
“…Exercise promotes a redistribution of blood flow, shunting it to the skeletal musculature and away from intraabdominal organs such as the liver (27). inferior wall (9)(10)(11)(12). With respect to the influence on myocardial counts from hot liver activity, the artifactual decrease in inferior activity is worse seems to be greater in higher liver activity.…”
Section: Pharmacological Versus Exercise Stressmentioning
confidence: 99%
“…Compared to exercise stress, pharmacological stress has shown a high liver uptake of 99m Tc perfusion radiopharmaceuticals (7,8). Such high liver uptake may create artifactual defects in the inferior wall with filtered back-projection reconstruction (9)(10)(11)(12). We hypothesized that pharmacological and exercise stress may show different improvements in the inferior wall in a prone SPECT study.…”
mentioning
confidence: 99%